Defect Chemistry of Highly Defective La0.1Sr0.9Co0.8Fe0.2O3-δ by Considering Oxygen Interstitials. Issue 14 (18th November 2016) - Im, Ha-Ni; Singh, Bhupendra; Hong, Jae-Woon; Kim, In-Ho; Lee, Kang Taek; Song, Sun-Ju
Abstract : In case of highly defective perovskite oxides such as La0.1 Sr0.9 Co0.8 Fe0.2 O3-δ (LSCF1982), the ionic defect has been in question by suggesting direct oxygen ion diffusion by considering lattice oxygen site as an interstitial rather than an oxygen vacancy. In the present study, the thermomigration of ionic defect species was measured by ionic thermopower measurement to provide strong evidence of interstitial diffusion and the defect structure was further analyzed in terms of effectively negatively charged oxygen interstitial as a charge-compensating defect against hole. Two kinds of holes-delocalized and localized at B-site cations; were investigated by defect chemical analysis. From the conductivity analysis based on the non-stoichiometry results, the contributions of delocalized holes, localized hole at Co site, localized hole at Fe site, and localized hole moving from Co site to Fe site were successfully separated, and it was observed that the hopping reaction involving hole localized at Co is dominant in conductivity mechanism. The measurement of electronic thermopower further confirms the involvement of two different types of holes in p-type conduction.